PKM for MSME Actors Through Creative Economy-Based Business Development and Digital Marketing in MSMEs Fostered by the Jambi Province Culture and Tourism Office - Helmi, sulaiman; Ariana, Sunda; Gunarto, Muji; Sofyan, Yayan; Marina, Marina (International Journal of Community Service & Engagement, 2025)
The main objective of Community Service (PKM) is to disseminate knowledge to the community around the University. In addition, the objective of Community Service (PKM) is to bring educational institutions closer to the community, so that universities can assist the government in accelerating the pace of the community's economy and preparing quality development cadres. The target of this Community Service (PKM) activity is counseling and training for Creative Economy Actors of UMKM in Jambi Province. This aims to increase the knowledge of the community and the benefits of this service can be received by Creative Economy Actors of UMKM. Digital marketing has been proven to provide various benefits, such as lower costs, wider market reach, and direct interaction with consumers